(untitled) (Al-Qamar, 2024)
Kalam-i-Iqbal is not less than Jam-i-Jahan-nama. It has thousands of figures of letters and sounds. Their study takes the reader into a world of understanding where the limits of perception expand. There are many forms of figure carving in the intellectual and artistic world of Danai-e-Raz. If we mention personal situations, the figures of Mirza Baidal, Ghalib and Sir Syed will appear. Mirza Baidal’s conscious and thought-filled points influenced Iqbal’s mind. Iqbal always kept his thoughts burning with the candle of Ghalib’s closeness. The thought of Sir Syed played the role of the most important source for the expansion of Iqbal’s thoughts, ideas and objectives. Studying this article will provide an extension to the topics of Iqbal Studies. Its study will create openness in the topics for criticism. The sources of this article will inspire the study of international works to broaden the scope of Iqbal Studies.